Factors Affecting the Organizational Silence of Academics Employed at the Universities in Pakistan - Nas, Zekeriya (Muş Alparslan Üniversitesi, 2021)
This study aims to reveal various factors affecting the organizational silence of academics employed at the universities in Pakistan. The teaching staff of the universities in Pakistan is among the most experienced and intellectual individuals and represents the elite sections of the society and the nation. For this reason, their opinions are considered to be very important for the generations of posterity. The teaching staff at the universities is also composed of planners, analysts, supervisors, and evaluators. The survey was conducted on 410 teaching staff such as lecturers, assistant professors, associate professors, and professors of various universities from six different provinces: public, private, and army. The data were analyzed through the Statistical Business Analyst (SAS) program. Organizations generally hire employees who have some experience, ideas, knowledge in order to develop their organizations. In summary, it can be said that there are generally two options for the staff working in any organization when perceiving wrongdoing in their workplace. They must either decide to speak up or continue to be silent. It is a fact that there is a prevalence of wrongdoings in every kind of organization, but unfortunately, not a lot is known about the decision making of staff related to this practice. While trying to find out factors affecting organizational silence, the observers believe that fear is one of the main factors in staff decisions to be silent about the issues and concerns in organizations. To overcome organizational silence, polyphony is accepted as one of the ways to solve the existing problem

Bu araştırmanın amacı, Pakistan'daki üniversitelerde görev yapan akademisyenlerin örgütsel sessizliğini etkileyen farklı faktörleri ortaya çıkarmaktır. Pakistan'daki üniversitelerin öğretim üyeleri, toplumun ve milletin seçkin kesimlerini temsil etmenin yanı sıra en deneyimli ve entelektüel kişiler arasındadır. Bu nedenle onların görüşleri gelecek nesiller için çok önemli kabul edilmektedir. Üniversitelerdeki öğretim üyeleri aynı zamanda planlamacılardan, analistlerden, denetçilerden ve değerlendiricilerden oluşmaktadır. Çalışma altı eyaletten çeşitli kamu, özel ve askeri üniversitelerde çalışan Okutman, Yardımcı Doçent, Doçent ve Profesör 410 öğretim elemanı üzerinde gerçekleştirilmiştir. Veriler İstatistiksel İş Analisti (SAS) paket programıyla analiz edildi. Organizasyonlar, genellikle kendilerini geliştirmek amacıyla bazı deneyimlere, fikirlere ve bilgiye sahip olan elemanları işe alırlar. Özetle, herhangi bir kuruluşta çalışanlar işyerinde yanlış bir şey algıladıklarında kendileri için genel olarak iki seçenek olduğu söylenebilir; ya çekinmeden konuşmalılar ya da sessiz olmaya devam etmelidirler. Her türlü kuruluşta yanlış yapmanın yaygın olduğu bir gerçektir ancak, bu uygulama ile ilgili personelin karar verme süreci hakkında ne yazık ki çok fazla şey bilinmemektedir. Araştırmacılar, örgütsel sessizliği etkileyen faktörleri bulmaya çalışırken, örgütlerdeki sorunlar ve endişelerle ilgili personelin sessiz kalmasına karar vermelerinde korkunun ana etkenlerden biri olduğuna inanmaktalar. Örgütsel sessizliği yenmek için çokseslilik, mevcut sorunu çözmenin yollarından biri olarak kabul edilir.
Pakistan'daki Üniversitelerde Çalışan Akademisyenlerin Örgütsel Sessizliğini Etkileyen Faktörler
anemon
Keywords: Academician; Factor; Organization; Organizational silence; University; Akademisyen; faktör; organizasyon; örgütsel sessizlik; Üniversite